Acid and enzymatic hydrolysis mediated bioethanol production from biomass of a noxious weed‐Parthenium hysterophorus L. Issue 1 (6th October 2016) - Gupta, Gaurav; Gour, Vinod Singh; Sharma, Paras; Kothari, S L.
Abstract : Parthenium hysterophorus, is a perennial herb, found throughout the world and considered as weed. It causes reduced productivity of soil and health hazards to cattle as well as human. But, easily available biomass of this weed offers a cost effective source, which can be used in lignocellulosic biofuel production. Biofuel is in great demand because as a renewable source of energy it can partly fulfill the growing demand of fuel in the era of global industrializations. In the present study, experiments have been designed and carried out to explore the potential of Parthenium hysterophorus as a source of biomass to produce bioethanol. Cellulose and hemicellulose of leaf and stem biomass of P. hysterophorus are converted to sugars using acid and enzymatic hydrolysis. These sugars are then subjected to fermentation using Saccharomyces cerevisiae. The results indicate that enzymatic hydrolysis of plant material is better as compared to acid hydrolysis. The maximum production of 219.67μL/mL ethanol is found in enzymatically hydrolyzed mixture of leaves and stem (1:1 w/w). In acid hydrolyzed material, the maximum yield of ethanol is found in leaf biomass (157.57 μL/mL). Therefore, utilization of enzymatic hydrolysis of P. hysterophorus derived plant materials would be an eco‐friendly approach for bioethanol production . © 2016 American Institute of Chemical Engineers Environ Prog, 36: 294–296, 2017